2009
DOI: 10.1123/jce.2.1.99
|View full text |Cite
|
Sign up to set email alerts
|

A Collaboration Model for Knowledge Transfer from Sport Science to High Performance Canadian Interuniversity Coaches

Abstract: This study examined the extent to which improved collaboration between sport scientists and coaches of high performance athletes might improve knowledge transfer in sport. The research includes a review of the extant literature on collaboration to develop a model of successful collaborative practice. The model is then empirically tested to determine whether such a model can improve our knowledge of the mechanisms for effective knowledge transfer in sport. To accomplish our purpose, we interviewed 38 high perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…It does not seem unreasonable to hazard a guess that coaches with higher levels of certification and those in the high-performance domain are more likely to reflect on and challenge their practice, and therefore, be open to new knowledge. Reade and Rodgers (2009) propose that a collaborative approach with sport scientists will increase the likelihood of knowledge transfer to coaches. Williams and Kendall (2007) found that research did not meet the needs of coaches, partly because of not using "lay" language and the need for more appropriate dissemination.…”
Section: Sports Sciencementioning
confidence: 99%
“…It does not seem unreasonable to hazard a guess that coaches with higher levels of certification and those in the high-performance domain are more likely to reflect on and challenge their practice, and therefore, be open to new knowledge. Reade and Rodgers (2009) propose that a collaborative approach with sport scientists will increase the likelihood of knowledge transfer to coaches. Williams and Kendall (2007) found that research did not meet the needs of coaches, partly because of not using "lay" language and the need for more appropriate dissemination.…”
Section: Sports Sciencementioning
confidence: 99%